EFFECTIVENESS OF ULTRA PETITUM PARTIUM IN DIVORCE CLAIMS IN RELIGIOUS COURTS - Nurhidayati, Nurhidayati; Liberty, Amira Fauziah; Nugraha, Satriya; Angkasa, Nawa; Sari , Fitri Maulina (Indonesian Association of Islamic Family Law Lecturers, 2022)
The ultra petitum partiumis a principle that doesn’t allow judge to make verdicts on unrequested or over-demanding cases. In divorcement cases, ithas limited the authority of the judge in giving verdicts to grant women's rights. The existence of a Supreme Court Circular Letter (SEMA) on number 3 of 2018 strengthened by PERMA on number 3 of 2017 concerning The Guidelines for Prosecuting Women Facing the Law opens a gap for judges to consider this principle. The type of this research is empirical legal research. The data obtained through field research and qualitative descriptive. The primary data sources in this study were collected through observations, and judges interview in the Metro Religious Courts. The secondary data sources are acquired from library (legislation and certain related books). The data analysis method conducted in 3 stages, 1. Collecting the data, 2.Restating the statement, and 3. Connecting the datawith existed theories. The results shows that the Metro Religious Court Judges still override the existence of a Supreme Court Circular (SEMA) number 3 of 2018 because it is only limited to the formulation of rooms that are not binding as legislations. It is may also be applied or ignored.